Individual sex-based variability to altitude training in elite badminton players - Précart, C.; Bouten, J.; Giroux, C.; Morales-Artacho, A.; Rousseau, Q.; Rabita, G.; Brocherie, F. (Journal of Sports Sciences, 2024)
To assess how altitude training impacts force-velocity-power (F-V-P) profiling and muscular power and anaerobic capacity in elite badminton players in reference to intra- and inter-individual sex-based variability. Following a quasi-experimental design, 14 players (6 females, 8 males) from the French national badminton singles and doubles teams performed a 3-week `living high-training high` camp at natural altitude (2320 m). F-V-P profile and Wingate anaerobic test were assessed Pre- and Post-intervention, using ANOVA repeated measures conventional statistics, with further estimation statistics to show the magnitude of the testing condition and visualize intra- and inter-individual responses. No significant interaction nor time effect (Pre- vs. Post-) was observed for any variables (all p > 0.05), but a significant sex effect was observed for maximal theoretical velocity (p < 0.01), relative maximal theoretical power (Pmaxrel) (p = 0.02) and relative F-V-P profile and for peak and mean power outputs (both p < 0.001) during Wingate test. Pre-to-Post changes (from -11.0% to + 14.4%) did not significantly differ between sexes, except for Pmaxrel (p < 0.05) in favor of female athletes (+10.2% vs. -4.3% for male athletes). Hedge`s g effect sizes (male minus female) revealed moderate and large effects for F-V-P profiling-derived variables. Mean conventional statistics did not reveal significant effect of altitude training, mainly due to high intra- and inter-variability across F-V-P profiling-derived variables and Wingate test. Substantial sex-based difference contributes to this variability, emphasizing the importance of individualized approach to enhance participant responsiveness to altitude training.